Romanian Perspective on Customer Loyalty for Direct Selling Companies - Claudia Bobalca (CES Working Papers, 2014)
The purpose of the research is to investigate Romanian direct sellers' perceptions on customers' loyalty. The research objectives are: (1) to identify the direct sellers' perceptions on the concept of loyalty; (2) to identify the main loyalty techniques that direct sellers use in their work with the clients; (3) to frame the portrait of a loyal customer. As a research method, we used qualitative research based on depth interviews. It is an exploratory and instrumental research, the results being used for building a questionnaire for a future survey. The investigated population is represented by direct selling women, with ages beteeen 19 and 30 years. For direct sellers, loyalty is an attitude and also a behavior, it means buying from the same company, from the same seller and preferring the products of the company. The main loyalty techniques that direct sellers use in their work with the clients are: promotional actions, personalization the relation with the client and offering stimulants. The loyal customer is the one who buys companies' products every month or at least quarterly, spends a monthly amount of 100 Ron on these products, works with the same seller, pays on time for the order, doesn't look only after promotions, loves the products, recommends the company to others, doesn't return the order, wants to buy more products from the company and trusts its products.
Keywords: M31; 330; loyal customer; direct selling; qualitative research; cosmetics products